Reinvestigation of the substrate specificity of a reverse prenyltransferase NotF from Aspergillus sp. MF297-2 - Yang, Keyan; Li, Shu-Ming; Liu, Xiaoqing; Fan, Aili (Archives of microbiology, 2020)
NotF from Aspergillus sp. MF297-2 and BrePT from Aspergillus versicolor catalyze a reverse C2-prenylation of brevianamide F in the biosynthetic pathway of brevianamides and notoamides. NotF was reported to use only brevianamide F as substrate while BrePT demonstrated broad substrate promiscuity. With high identity at amino acid level, it is interesting to reinvestigate the catalytic activities of these two prenyltransferases in vitro toward 14 cyclodipeptides. Product identification of the in vitro assays by MS proved that NotF and BrePT share similar catalytic ability and substrate promiscuity.